A new Pacific Ocean species of Typhlonida Macpherson & Baba, 2022 (Crustacea, Decapoda, Munididae) from the flank of the emergent seamount Isla del Coco (Costa Rica) with notes on the phylogeny of the genus - Dong Dong; Charlotte A. Seid; Xinzheng Li; Greg W. Rouse (Zoosystematics and Evolution)
The genus Typhlonida Macpherson & Baba in Machordom et al. 2022 is a group of munidid squat lobsters typically found in deep waters. This study describes and illustrates a new species, Typhlonida cocoensis sp. nov., from a seamount area in the eastern Pacific. Typhlonida cocoensis sp. nov. is closely related to T. sanctipauli (Henderson, 1885) but can be readily distinguished from the latter by its relatively small eyes, narrow anterior margin of the thoracic sternite 4, lack of granules on the lateral surfaces of sternite 7, and unarmed anterior branchial regions dorsally. In addition to morphological comparisons, genetic distance and phylogenetic analyses were used to support the recognition of this new species. The phylogenetic positions of the Typhlonida and Antillimunida species from the eastern Pacific are discussed.